Relationship status and mental and physical health among Polish and American young adults: The role of relationship satisfaction and satisfaction with relationship status. Issue 3 (17th February 2021) - Adamczyk, Katarzyna; Barr, Ashley B.; Segrin, Chris
Abstract: There is growing recognition that relationship factors besides relationship status play an important role in young adults' mental and physical health. This study explored the concurrent (between‐individual) and longitudinal (within‐individual) associations between relationship status, relationship satisfaction, satisfaction with relationship status, and varied dimensions of health in samples of Polish and U.S. young adults. Data from young adults (aged 18–34 at Wave 1) were collected in a three‐wave investigation in Poland and in the USA with one‐year intervals between each of the measurements. The cross‐sectional analyses demonstrated that individuals in relationships reported better health, particularly if they were in a higher‐quality relationship. The fixed‐effects models showed that relationship quality was a much more consistent and powerful predictor of health than was relationship status; however, for depression, satisfaction with relationship status was an independent contributor to health. Cross‐cultural analyses revealed a stronger link between partner status and depression and emotional well‐being, and relationship satisfaction and psychological well‐being among Polish young adults than their American counterparts. The results demonstrated that characteristics of relationships and satisfaction with relationship status matter more for changes in health than relationship status alone and that these links may differ by cultural context.